The Effects of Perchlorates on the Permafrost Methanogens: Implication for Autotrophic Life on Mars - Viktoria Shcherbakova; Viktoria Oshurkova; Yoshitaka Yoshimura (Microorganisms, 2015)
The terrestrial permafrost represents a range of possible cryogenic extraterrestrial ecosystems on Earth-like planets without obvious surface ice, such as Mars. The autotrophic and chemolithotrophic psychrotolerant methanogens are more likely than aerobes to function as a model for life forms that may exist in frozen subsurface environments on Mars, which has no free oxygen, inaccessible organic matter, and extremely low amounts of unfrozen water. Our research on the genesis of methane, its content and distribution in permafrost horizons of different ages and origin demonstrated the presence of methane in permanently frozen fine-grained sediments. Earlier, we isolated and described four strains of methanogenic archaea of Methanobacterium and Methanosarcina genera from samples of Pliocene and Holocene permafrost from Eastern Siberia. In this paper we study the effect of sodium and magnesium perchlorates on growth of permafrost and nonpermafrost methanogens, and present evidence that permafrost hydogenotrophic methanogens are more resistant to the chaotropic agent found in Martian soil. In this paper we study the effect of sodium and magnesium perchlorates on the growth of permafrost and nonpermafrost methanogens, and present evidence that permafrost hydogenotrophic methanogens are more resistant to the chaotropic agent found in Martian soil. Furthermore, as shown in the studies strain M2T M. arcticum, probably can use perchlorate anion as an electron acceptor in anaerobic methane oxidation. Earth’s subzero subsurface environments are the best approximation of environments on Mars, which is most likely to harbor methanogens; thus, a biochemical understanding of these pathways is expected to provide a basis for designing experiments to detect autotrophic methane-producing life forms on Mars.